The Relationship Between Weight Perception, Gender, and Depressive Symptoms Among Rural Adolescents - Kathryn Puskar; Lisa Marie Bernardo; Carl Fertman; Dianxu Ren; Kirsti Hetager Stark (Rural Nurse Organization; Binghamton University, 2012)
Research findings indicate a relationship between weight perception and depression in adolescents. This study explored the relationship between weight perception, gender, and depressive symptoms in rural adolescents. Among 623 rural adolescents who completed a health inventory and a depression scale, 75 participants (n = 62 females; n = 13 males) had depressive symptoms and were used in data analysis. A two-way ANOVA model was used to evaluate the effects of weight perception and gender on depressive symptoms in rural adolescents. Although the 2-way ANOVA was not significant, there was a statistical significant finding for females who reported perceived weight problems and depression. The interaction between gender and weight perception was of marginal statistical significance (p = 0.07). Females who perceived a problem with their weight had higher depressive scores compared to females who did not perceive a problem with their weight (p = 0.0002), however no difference was observed for males. Implications are for rural nurses to screen adolescents for depressive symptoms and their weight perception during health care visits, with emphasis on females.